A study of the collection development policy of Quezon City Public Library - Rubiato, Joannalyn D. (School of Library and Information Studies, University of the Philippines Diliman, 2007)
Public libraries have a great responsibility in the community. these cater to different people from different walks of life and provide them materials that are educational and recreational. the Quezon City Public Library (QCPL) was established on August 16, 1948. It started as a small public library but is now the biggest public library maintained by a city government in Metro Manila. The QCPL has 16 branches around different barangays of Quezon City.